Agomelatine in Depressive Disorders: Its Novel Mechanisms of Action - Srinivasan, Venkataramanujan; Zakaria, Rahimah; Othman, Zahiruddin; Lauterbach, Edward C.; Acuña-Castroviejo, Darío (American Psychiatric Publishing, 2012)
Disruptions in sleep and sleep–wake cycle regulation have been identified as one of the main causes for the pathophysiology of depressive disorders. The search has been on for the identification of an ideal antidepressant that could improve both sleep disturbances and depressive symptomatology. Melatonin, the major hormone of the pineal gland, has been shown to improve sleep and is involved in the regulation of the sleep–wake cycle. Identification of high concentrations of MT1 and MT2 melatonergic receptors in the suprachiasmatic nucleus of the anterior hypothalamus, the structure concerned with regulation of circadian rhythms and sleep–wake cycles, has led to the development of melatonergic agonists with greater potency and longer durations of action. Agomelatine is one such melatonergic agonist that acts specifically on MT1/MT2 melatonergic receptors and at the same time exhibits 5-HT2C antagonism, a property that is utilized by current antidepressants that are in clinical use. Agomelatine has been shown to be effective in a number of animal models of depression.